'Running Away with Itself': Missionaries, Islanders and the Reimagining of Cricket in Samoa, 1830–1939. Issue 1 (2nd January 2017) - Sacks, Benjamin
ABSTRACT: Missionaries were among the first and most influential bearers of European social practices in Oceania. While they sought to reshape the lives of Indigenous peoples, missionaries frequently found that Islanders reconfigured introduced practices in distinctive and sometimes disruptive ways. This essay explores this process using the example of sport and games, and particularly cricket, in Samoa. Despite initial reservations, by the late-19th century most missionaries considered European sports to be inoffensive and even useful in furthering their objectives. Samoan pastimes, however, were irremediably bound to 'un-Christian' practices such as lewd dancing, revelry and excess. This neat dichotomy was disrupted by the manner in which Samoans adapted papalagi (foreign) sports – principally cricket – in ways that obliterated their European character and instead catered to Samoan expectations of what recreation should be. After initial efforts to control and proscribe cricket, missionaries grew resigned to its place within increasingly 'Samoanised' churches.